Arterial hypertension: prevalence, awareness, antihypertensive pharmaceutical treatment, treatment effectiveness in Russian population - S. A. Shalnova; Yu. A. Balanova; V. V. Konstantinov; T. N. Timofeeva; V. M. Ivanov; A. V. Kapustina; A. D. Deev (Российский кардиологический журнал, 2006)
The first-wave results of the Federal Program «Arterial Hypertension Prevention and Treatment in the Russian Federation» are presented. Randomized representative cluster samples from non-organized male and female population aged 15- 75+ years, residing in seven Federal Regions, have been studied (response rate above 80 %). Overall age-adjusted prevalence of arterial hypertension (AH) in Russia was 39, 5 % (in females, F, 40, 4 %, in males, M, 37, 2 %). AH awareness was as high as 77, 9 % (F 80, 3 %, M 75 %). Treatment rate was 59, 4 % (F 63, 1 %, M 53, 1 %), and effective treatment rate -just 21, 5 % (F 22, 5 %, M 20, 5 %). ACE inhibitors are the most frequently administered antihypertensive drugs (70, 7 %).